-1+3m+12=

Simple and best practice solution for -1+3m+12= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1+3m+12= equation:


Simplifying
-1 + 3m + 12 = 0

Reorder the terms:
-1 + 12 + 3m = 0

Combine like terms: -1 + 12 = 11
11 + 3m = 0

Solving
11 + 3m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 3m = 0 + -11

Combine like terms: 11 + -11 = 0
0 + 3m = 0 + -11
3m = 0 + -11

Combine like terms: 0 + -11 = -11
3m = -11

Divide each side by '3'.
m = -3.666666667

Simplifying
m = -3.666666667

See similar equations:

| y=-4(-3)-12 | | 1=(2x+45) | | Log(x)=-7 | | 6x-4+8x-12=180 | | 3n+3+24n= | | (2p-5)+(p+2)=45 | | 2x+5=113 | | (2ab^2)(3ab)=x | | 5+3=12t | | 6t-7=53 | | 5b+6=-1 | | (-8x+1)-(7x-1)= | | 5x^2+5y^2-40x-20y-25=0 | | 2z-14=-49+9z | | X-0.25x=79.63 | | -3p-8-4p= | | 5a-6=8a-9 | | 3x-15=-15+x | | -9x+9+3x=-10x-3 | | .6(n+25)=10+.4n | | 2x+5(-4x-12)=-6 | | 4y+30=180 | | 1n-2-2n= | | 2(2x-6)=2 | | 800=100x-0.5x^2 | | 5+3*(-6)/(-3)= | | (-4x+3)+(2x+8)= | | 5=4y-3y | | 7(-4-t)=-84 | | 12x+13y=31.571 | | 4x-5y=420 | | x=(2x-1)-5 |

Equations solver categories